2011
DOI: 10.1097/gme.0b013e318215101a
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis screening and treatment guidelines

Abstract: In this prospective study, depression-detected by a validated three-item questionnaire-was able to predict those women more likely to develop CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 11 publications
1
18
0
5
Order By: Relevance
“…10 In a survey of women referred for DXA screening at one center, over 40 % of screened women under the age of 65 years did not meet criteria for screening. 11 However, to our knowledge, the degree of DXA overuse across an entire screening population has not been reported.…”
Section: Introductionmentioning
confidence: 81%
“…10 In a survey of women referred for DXA screening at one center, over 40 % of screened women under the age of 65 years did not meet criteria for screening. 11 However, to our knowledge, the degree of DXA overuse across an entire screening population has not been reported.…”
Section: Introductionmentioning
confidence: 81%
“…BMD of different national groups have differences, which have been recognized by level of development and national medical standards. [18][19][20]. At the same time, reports about the prevalence of osteoporosis were very different, and this difference may also be related to the race groups in the population.…”
Section: Discussionmentioning
confidence: 94%
“…Prior research has shown that, among 944 healthy women in Ontario referred for a baseline DXA test at midlife, more than 90% had normal bone density. 12 Similarly, in a US cohort of 615 women aged 49 years or more who received a baseline DXA test, Schnatz and colleagues 13 found that 40% did not meet the North American Menopause Society criteria for testing. 2 In a recent study involving 4957 women aged 67 years or more with normal bone mineral density or osteopenia, osteoporosis was detected in less than 10% during rescreening intervals of about 15 years.…”
Section: Discussionmentioning
confidence: 99%